Herpes Simplex Virus Cell Entry Mechanisms: An Update - Madavaraju, Krishnaraju; Koganti, Raghuram; Volety, Ipsita; Yadavalli, Tejabhiram; Shukla, Deepak (Frontiers in Cellular and Infection Microbiology, 2021)
Herpes simplex virus (HSV) can infect a broad host range and cause mild to life threating infections in humans. The surface glycoproteins of HSV are evolutionarily conserved and show an extraordinary ability to bind more than one receptor on the host cell surface. Following attachment, the virus fuses its lipid envelope with the host cell membrane and releases its nucleocapsid along with tegument proteins into the cytosol. With the help of tegument proteins and host cell factors, the nucleocapsid is then docked into the nuclear pore. The viral double stranded DNA is then released into the host cell’s nucleus. Released viral DNA either replicates rapidly and produces viral progeny (more commonly in non-neuronal cells) or stays latent inside the nucleus (in sensory neurons). The fusion of the viral envelope with host cell membrane is a key step. Blocking this step can prevent entry of HSV into the host cell and the subsequent interactions that ultimately lead to production of viral progeny and cell death or latency. In this review, we have discussed viral entry mechanisms including the pH-independent as well as pH-dependent endocytic entry, cell to cell spread of HSV and use of viral glycoproteins as an antiviral target.